Swelling kinetics and electrical charge transport in PEDOT:PSS thin films exposed to water vapor. (8th May 2018) - Sarkar, Biporjoy; Jaiswal, Manu; Satapathy, Dillip K
Abstract: We report the swelling kinetics and evolution of the electrical charge transport in poly(3, 4-ethylene dioxythiophene) polystyrene sulfonate (PEDOT:PSS) thin films subjected to water vapor. Polymer films swell by the diffusion of water vapor and are found to undergo structural relaxations. Upon exposure to water vapor, primarily the hygroscopic PSS shell, which surrounds the conducting PEDOT-rich cores, takes up water vapor and subsequently swells. We found that the degree of swelling largely depends on the PEDOT to PSS ratio. Swelling driven microscopic rearrangement of the conducting PEDOT-rich cores in the PSS matrix strongly influences the electrical charge transport of the polymer film. Swelling induced increase as well as decrease of electrical resistance are observed in polymer films having different PEDOT to PSS ratio. This anomalous charge transport behavior in PEDOT:PSS films is reconciled by taking into account the contrasting swelling behavior of the PSS and the conducting PEDOT-rich cores leading to spatial segregation of PSS in films with PSS as a minority phase and by a net increase in mean separation between conducting PEDOT-rich cores for films having abundance of PSS.